2015
DOI: 10.3310/hsdr03310
|View full text |Cite
|
Sign up to set email alerts
|

Care and communication between health professionals and patients affected by severe or chronic illness in community care settings: a qualitative study of care at the end of life

Abstract: (2015) Care and communication between health professionals and patients affected by severe or chronic illness in community settings: a qualitative study of care at the end of life. Health Services Delivery and Research, 3 (31). ISSN 2050-4349 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/35464/2/FullReport-hsdr03310.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 133 publications
2
63
0
1
Order By: Relevance
“…ACP is described as a key to improve the experience of dying and death by enabling patients to consider end-of-life care options and preferences [64], but an ACP-discussion might also include the individual patient’s concerns and wishes [65]. We found that when the observed conversations turned to issues concerning the future and end-of-life care, the questions raised by the physician covered questions concerning medical treatment and/or hospitalization, where the patients seemed to struggle to answer clearly.…”
Section: Discussionmentioning
confidence: 99%
“…ACP is described as a key to improve the experience of dying and death by enabling patients to consider end-of-life care options and preferences [64], but an ACP-discussion might also include the individual patient’s concerns and wishes [65]. We found that when the observed conversations turned to issues concerning the future and end-of-life care, the questions raised by the physician covered questions concerning medical treatment and/or hospitalization, where the patients seemed to struggle to answer clearly.…”
Section: Discussionmentioning
confidence: 99%
“…However, until resources are in place to adequately and equitably support home deaths, the current promotion of patient choice risks raising expectations that are not realised. 46 There are many reasons why patients may not wish to die at home. Death at home is not necessarily good, and just because a patient did not die at home does not necessarily mean their death occurred in the wrong place.…”
Section: Resultsmentioning
confidence: 99%
“…Covid-19 guidance on advance care planning has largely focused on its product: a plan recording an individual’s treatment preferences 34. Yet evidence suggests that some of the main benefits that frail patients and their loved ones experience from advance care planning are strengthened relationships with each other and their clinical teams, and support through the experiences of living and dying with frailty and bereavement 6789. These benefits come largely from the conversations that constitute the planning process, particularly when these occur over time and include the patient’s family and loved ones.…”
Section: Process Versus Productmentioning
confidence: 99%